2011
DOI: 10.1007/s00477-011-0540-2
|View full text |Cite
|
Sign up to set email alerts
|

Wave height characteristics in the north Atlantic ocean: a new approach based on statistical and geometrical techniques

Abstract: The main characteristics of the significant wave height in an area of increased interest, the north Atlantic ocean, are studied based on satellite records and corresponding simulations obtained from the numerical wave prediction model WAM. The two data sets are analyzed by means of a variety of statistical measures mainly focusing on the distributions that they form. Moreover, new techniques for the estimation and minimization of the discrepancies between the observed and modeled values are proposed based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…This may lead to different behavior of the GPD shape and scale parameters. Galanis et al [35] found that the GPD was close to a straight line (in the Gumbel space) when offshore wave data was analysed. wave buoys are located further away from the coast than others with similar level of exposure.…”
Section: Wave and Storm Event Identificationmentioning
confidence: 90%
“…This may lead to different behavior of the GPD shape and scale parameters. Galanis et al [35] found that the GPD was close to a straight line (in the Gumbel space) when offshore wave data was analysed. wave buoys are located further away from the coast than others with similar level of exposure.…”
Section: Wave and Storm Event Identificationmentioning
confidence: 90%
“…However, this is not universally distributed along the globe; further exploration regional analysis must be undertaken to determine the metocean characteristics accurately. Long-term high fidelity spatio-temporal data are very important for analysis on wave conditions [5], wave power resource [6], extreme value analysis [1,7], and climate characteristics [3,8], etc.To obtain necessary information, for climate analysis on any type of renewable resource, a minimum duration of 10 years is required [9][10][11][12][13]. Furthermore, to have a good understanding of climate conditions and their persistence, additional considerations on Climatological Standard Normals (CSN) are required.…”
mentioning
confidence: 99%
“…However, this is not universally distributed along the globe; further exploration regional analysis must be undertaken to determine the metocean characteristics accurately. Long-term high fidelity spatio-temporal data are very important for analysis on wave conditions [5], wave power resource [6], extreme value analysis [1,7], and climate characteristics [3,8], etc.…”
mentioning
confidence: 99%
“…under the initial conditions !.0/ D f 1 , !.1/ D f 2 , with all the non-linear part providing a clear difference from the case of least square approach (see for more details [5,7]). a 0,i a 1,i a 2,i : : : a n,i…”
Section: Information Geometry Tools For Optimization Modelsmentioning
confidence: 99%